2020
DOI: 10.1177/0306624x20919714
|View full text |Cite
|
Sign up to set email alerts
|

“You Have to Separate the Sinner From the Sin”: Clinician’s Approaches to Psychological Assessments With Men who Have Sexually Offended

Abstract: Men who have sexually offended are often referred for presentence psychological assessments to determine factors which contributed to offending, identify risk of recidivism, and develop treatment recommendations. The accuracy of assessments is largely reliant on the cooperation of the assessee. Despite the significant legal and emotional consequences, how clinicians approach these assessments, attempt to engage assessees, and overcome resistance have not been investigated. This research sought to develop an un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…There is a small but growing body of qualitative (Chawke et al, 2020, 2021) and experimental (Vera et al, 2019) research examining evaluator empathy in forensic evaluations, all focusing on risk assessment interviews. Findings from one small qualitative study of court-ordered, presentence risk assessments of individuals convicted of sexual offenses suggested that evaluators ( N = 6) may have purposefully used empathy to encourage openness from evaluees, believing that failing to do so could lead evaluees to withdraw and leave evaluations lacking detail and depth (Chawke et al, 2020). These evaluators’ beliefs about empathy were supported by findings from evaluees ( N = 6), who reported that empathy from evaluators made them feel “at ease,” “free,” and “open” (Chawke et al, 2021, p. 12).…”
Section: Perspectives On the Use Of Evaluator Empathy In Forensic Ass...mentioning
confidence: 99%
See 2 more Smart Citations
“…There is a small but growing body of qualitative (Chawke et al, 2020, 2021) and experimental (Vera et al, 2019) research examining evaluator empathy in forensic evaluations, all focusing on risk assessment interviews. Findings from one small qualitative study of court-ordered, presentence risk assessments of individuals convicted of sexual offenses suggested that evaluators ( N = 6) may have purposefully used empathy to encourage openness from evaluees, believing that failing to do so could lead evaluees to withdraw and leave evaluations lacking detail and depth (Chawke et al, 2020). These evaluators’ beliefs about empathy were supported by findings from evaluees ( N = 6), who reported that empathy from evaluators made them feel “at ease,” “free,” and “open” (Chawke et al, 2021, p. 12).…”
Section: Perspectives On the Use Of Evaluator Empathy In Forensic Ass...mentioning
confidence: 99%
“…These evaluators’ beliefs about empathy were supported by findings from evaluees ( N = 6), who reported that empathy from evaluators made them feel “at ease,” “free,” and “open” (Chawke et al, 2021, p. 12). The evaluators did not believe they should be detached during evaluations and described a “therapeutic component” to their risk assessment interviews (Chawke et al, 2020, p. 1525). In the evaluators’ view, the risk assessment interviews provided evaluees with an opportunity to discuss uncomfortable issues (e.g., their own victimization) and the opportunity to gain insight into their offending behavior.…”
Section: Perspectives On the Use Of Evaluator Empathy In Forensic Ass...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Chawke et al., the therapeutic relationship that the patient achieves with the clinician can significantly influence the information shared with him (Chawke et al., 2021 ). Thus, from the point of view of the clinician who performs the FPA, obtaining a good rapport with the patient is essential to achieve a good clinical interview (Chawke et al., 2020 ). It is also of relevance to collect the information from the perspective of those evaluated in order to learn from their experience and thereby maximise the success of FPAs performed in this way.…”
Section: Introductionmentioning
confidence: 99%
“…Covid-19 pandemic, psychological assessment, qualitative research, remote assessment rapport with the patient is essential to achieve a good clinical interview (Chawke et al, 2020). It is also of relevance to collect the information from the perspective of those evaluated in order to learn from their experience and thereby maximise the success of FPAs performed in this way.…”
Section: Introductionmentioning
confidence: 99%